An Analysis of WhatsApp Smiley Emoji Usage and Interpretation Among St. Augustine University Students in Mwanza, Tanzania. - Joanita K. Rwezahula, (Technium Social Sciences Journal, 2026)
This study analyses the interpretation of emoji used in WhatsApp text messages among St. Augustine University students in Tanzania. The aim of this study is to determine whether there is a universal understanding of emoji usage. Mixed research approach used with sequential explanatory design. Purposive and simple random sampling used to get the participants of the study and data collected through questionnaires and focus group discussions. Data were analyzed by using both qualitative and quantitative methods of data analysis. The findings indicated that there is plenty of meaning interpretation for each smiley emoji. Out of the examined smileys emoji used as the variable in this research, only seven smileys emoji which are Love, kiss, lying, drooling, sleepy, crying, delicious, were interpreted similarly by all the respondents. The rest were interpreted differently according respondents’ understandings of the smileys' meaning. It is recommended to incorporate Emoji Studies into Digital Communication and Media Curricula, as emojis are now a fundamental part of digital communication. Academic institutions, especially media and communication schools, should integrate emoji interpretation into their curriculum. This will help students develop critical digital literacy skills, equipping them to analyse emoji use in various professional, academic, and social contexts.